1973
DOI: 10.1149/1.2403390
|View full text |Cite
|
Sign up to set email alerts
|

Resistivity of Doped Polycrystalline Silicon Films

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…If we assume the grains are cubes, Q,I NSi for silicon can be given by 1.62X 1O- 7 The solid lines are for N = 5 X 1O'9cm-3, while the behavior for N = 5 X 10 2°c m-3 is also shown for the smallest grain size (dashed line). If we assume the grains are cubes, Q,I NSi for silicon can be given by 1.62X 1O- 7 The solid lines are for N = 5 X 1O'9cm-3, while the behavior for N = 5 X 10 2°c m-3 is also shown for the smallest grain size (dashed line).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…If we assume the grains are cubes, Q,I NSi for silicon can be given by 1.62X 1O- 7 The solid lines are for N = 5 X 1O'9cm-3, while the behavior for N = 5 X 10 2°c m-3 is also shown for the smallest grain size (dashed line). If we assume the grains are cubes, Q,I NSi for silicon can be given by 1.62X 1O- 7 The solid lines are for N = 5 X 1O'9cm-3, while the behavior for N = 5 X 10 2°c m-3 is also shown for the smallest grain size (dashed line).…”
Section: Theorymentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] These investigations have shown that electrical properties of polycrystalline silicon are markedly different from those of single-crystal silicon. [1][2][3][4][5][6][7][8][9] These investigations have shown that electrical properties of polycrystalline silicon are markedly different from those of single-crystal silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, these films have been generally deposited in atmosphericpressure, cold-wall reactors, in which the silicon substrates lie fiat on an externally heated susceptor. The electrical properties of such films have been reported by many researchers (4)(5)(6)(7)(8).…”
Section: Hewlett-packard Laboratories Palo Alto Calilornia 94304mentioning
confidence: 99%
“…At higher B r , some boron atoms may segregate at the grain boundary in electrically inactive sites, resulting in a decrease of d and E a . [38][39][40] The increased amorphous tissue caused change in the FTIR peak, shifting from MSMs to LSMs, and increased HSMs.…”
Section: Effect Of the Diborane (B 2 H 6 ) Onmentioning
confidence: 99%